Sifat Fisik Dan Mekanik Mortar Dengan Penambahan Bakteri Bacillus Subtilis - Dian Nanda Islami; Zulfikar Djauhari; Enno Yuniarto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The development of construction technology has progressed quite rapidly, especially in the field of building materials. One form of technological advancement in building materials which has been developing until now is mortar. Mortar is a mixture of cement, fine aggregate, water and stirred until homogeneous. This study used Bacillus Subtilis as an added ingredient by examining it’s physical and mechanical properties, as well as an innovation in crack recovery in mortars using bacteria called self healing Mortar. Tests were carried out on normal mortar and bacterial mortar aged 28 and 56 days. The physical properties of the mortar tested were porosity, sorptivity and unit weight, while the mechanical properties tested were compressive strength. The results showed that the porosity value of bacterial mortality was smaller than that of normal mortality at 28 days and 56 days with a value of 12.53% and 11.8%. The results of the bacterial mortar unit weight test showed a greater value than normal mortar at the age of 28 days and 56 days with a value of 2.12 gr / cm3 and 2.184 gr / cm3. The soprtivity test results showed that the value of sorptivity mortar bacteria was lower at the age of 28 days and 56 days compared to normal sorptivity mortar with values of 0.1092 mm / min0.5 and 0.0861 mm / min0.5. The compressive strength test results showed that the compressive strength value of bacterial mortar was greater than normal mortar at the age of 28 days and 56 days with values of 20.94 MPa and 21.61 MPa. Based on these data, it can be concluded that the mortar with the addition of bacillus subtilis bacteria is better than normal mortar. Keyword : Mortar, Bacillus Subtilis, Physical Properties, Mechanical Properties, Self Healing